Autophagy of the Nucleus in Health and Disease - Konstantinidis, Georgios; Tavernarakis, Nektarios (Frontiers in Cell and Developmental Biology, 2022)
Nucleophagy is an organelle-selective subtype of autophagy that targets nuclear material for degradation. The macroautophagic delivery of micronuclei to the vacuole, together with the nucleus-vacuole junction-dependent microautophagic degradation of nuclear material, were first observed in yeast. Nuclear pore complexes and ribosomal DNA are typically excluded during conventional macronucleophagy and micronucleophagy, indicating that degradation of nuclear cargo is tightly regulated. In mammals, similarly to other autophagy subtypes, nucleophagy is crucial for cellular differentiation and development, in addition to enabling cells to respond to various nuclear insults and cell cycle perturbations. A common denominator of all nucleophagic processes characterized in diverse organisms is the dependence on the core autophagic machinery. Here, we survey recent studies investigating the autophagic processing of nuclear components. We discuss nucleophagic events in the context of pathology, such as neurodegeneration, cancer, DNA damage, and ageing.